ANY LINKS BETWEEN ECONOMIC PERFORMANCE AND INSTITUTIONAL QUALITY? EVIDENCE FROM VIETNAM PROVINCES AND CITIES - Nhan, Le Trung; Tung, Nguyen Van (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2017)
This study aims at finding possible links between the economic performance and institutional quality of provinces and cities in Vietnam by using regression analysis. The economic performance is measured by Net revenue of all firms in each province or city. The institutional quality is representative with Provincial Competitiveness Index (PCI) of respective province or city. For regression models, while the dependent variable is economic performance of provinces, PCI is used as the key independent variable. Labor and capital are main production factors of the economic performance, so they are also included in the regression models. The data of the years 2012 and 2013 collected from sixty-three provinces and cities in Vietnam is used in the study. The study shows a link between the economic performance and the institutional quality of provinces and cities in Vietnam.